The argumentative and consecutive of the conjunction tool (Even) (Hataa) as in Surah of Al-Baqarah as a model - Hamid Mustafa, Abdulrazzaq; Hamid Mustafa, Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
In this Qur'anic discourse, the effect of the conjunction (Hataa) appears in creating and building those contexts, as from the linguistic structure that manifests the psychological state of the marriage of the woman to another man, and Allah Almighty words come after (Hataa) (until she has wed another spouse), indicating another contextual feature, which is the psychological state of the man in that state, and by linking the arguments before and after (Hataa), we get the psychological background and the harsh lesson for them. AlShaarawi says: "If matters between the couple reach the point of no return, there must be a hard lesson; neither can go back easily. Allah gave them the legislation of the minor irrevocable divorce followed by a new dowry and a contract, so it was necessary for the major irrevocable divorce, and the great judgment had to be that women married another spouse and tried another marital life. The lesson is harsh.